Researching the Possibility and Authenticity of Systematization in Jurisprudence (With an Emphasis on ShahÄ«d á¹¢adrâs Outlook) - Ã˜Â¹Ã™Â„Ã›ÂŒ Ã˜Â§ÃšÂ©Ã˜Â¨Ã˜Â±Ã›ÂŒ Ã˜Â¨Ã˜Â§Ã˜Â¨Ã™ÂˆÃšÂ©Ã˜Â§Ã™Â†Ã›ÂŒ, Ã˜Â§Ã˜ÂÃ˜Â³Ã˜Â§Ã™Â†; Ã˜Â·Ã˜Â¨Ã˜Â§Ã˜Â·Ã˜Â¨Ã˜Â§Ã˜Â¦Ã›ÂŒ, Ã˜Â³Ã›ÂŒÃ˜Â¯ Ã™Â…Ã˜ÂÃ™Â…Ã˜Â¯Ã˜ÂµÃ˜Â§Ã˜Â¯Ã™Â‚; Ã˜Â¢Ã™Â‡Ã™Â†ÃšÂ¯Ã˜Â±Ã›ÂŒ, Ã˜Â§Ã˜ÂÃ˜Â³Ã˜Â§Ã™Â† (Ã™ÂÃ™Â‚Ã™Â‡ Ã™Âˆ Ã˜Â§Ã˜ÂµÃ™ÂˆÃ™Â„)
One of the most important issues in jurisprudence that has to be researched is to find out whether the Islamic rulings are unique notions (mufradÄt) without any correlation or collections with deep relations and forming an integrated system. The writers in this article maintain that there is a very profound relation among the collection of rulings, which in every field, when considered together, constitute an integrated system that enjoys unique principles and purposes, whose unveiling is among the ability, or better say the duties, of a master jurist (mujtahid). Thus, with an emphasis on the viewpoint of ShahÄ«d á¹¢adr, who is somehow considered as the innovator of this idea, we intend to explain the method of achieving the system. ShahÄ«d á¹¢adrâs idea has not been so far taken into consideration and elucidated as a pattern for jurisprudential systematization and the new perspective of the present writing is directed toward this goal. The system that is discovered by a master jurist needs to achieve authenticity and confirmation by the lawmaker, just as any ruling that he implies from the evidences. Although ShahÄ«d á¹¢adr has not discussed much in this field, we have proceeded to prove its authenticity in the conclusion of our discussion.